Final-year medical students' reflections on types of significant events in primary care - Samantha Dube; Motlatso Mlambo; Nontsikelelo O. Mapukata O. Mapukata (AOSIS, 2023)
Background: Adverse events are considered a universal challenge and a burden in the provision of healthcare. For that reason, significant event analysis (SEA) is a critical undertaking in primary health care (PHC), particularly in South Africa where 84% of the population relies on the public health system for their care. Aim: The study aimed to describe the types of perceived significant events medical students experienced during an integrated primary care block placement. Setting: Eighteen PHC settings included clinics, community health centres and district hospitals across three provinces in Gauteng, Mpumalanga and the North West. Methods: Using a qualitative descriptive design with purposeful sampling and maximum variation, structured reflection reports were retrieved from logbooks of final-year medical students studying at a South African university in 2014. Conventional content analysis was used to record the relevant facets of secondary data from 124 logbooks that contained a recording of a significant event using MAXQDA software version 2020.4. Results: An iterative process revealed three major themes of significant events that were prevalent in PHC settings. These comprised medication and prescription errors, diagnostic errors and suboptimal patient management. Conclusion: Significant event analysis became a critical quality improvement reflective learning tool. Logbooks offered an opportunity for medical students to explore significant events as a strategic way towards addressing quality and safe practices in PHC settings. Contribution: This study demonstrated medical students' ability to identify incidents in the care of patients using the SEA approach and their role in assessing patient safety issues in PHC settings.